The Association Between Marital Satisfaction, Depression, and Sexual Dysfunction Scores among Women at Six Months Postpartum in Kelantan, Malaysia - Ng, Ying Ying; Muhamad , Rosediani; Ahmad, Imran (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Female sexual dysfunction (FSD) can significantly impact the quality of sexual relationships, potentially leading to marital dissatisfaction and depression if it occurs postnatally. However, there is limited research investigating FSD, marital satisfaction, and postnatal depression (PND) in Malaysia. This study aimed to determine the association between FSD scores with marital satisfaction scores and depression scores among postpartum women in Kota Bharu, Kelantan. MATERIALS AND METHODS: A cross sectional study was conducted among 429 women at 6 months postpartum in four primary healthcare clinics in Kota Bharu district. They were required to answer the Malay Version of the Female Sexual Function Index-6 (MVFSFI-6), Golombok Rust Inventory of Marital State (MV-GRIMS), and the Edinburgh Postnatal Depression Scale (MV-EDPS). The data was analysed using multiple linear regression. RESULTS: At six months postpartum, 52.5% were at risk of sexual dysfunction, 55.0% at risk of marital dissatisfaction, and 18.2% at risk of PND. The associations between FSD scores and marital dissatisfaction scores, as well as FSD scores and PND scores, were significant. CONCLUSION: The frequency of FSD could heighten the risks of marital dissatisfaction and depression in postpartum women. Thus, healthcare providers should holistically assess sexual issues in postpartum women and refer them for early diagnosis and treatment to prevent adverse outcomes.